2005
DOI: 10.1017/s1355617705050836
|View full text |Cite
|
Sign up to set email alerts
|

Workers' risk of unemployment after traumatic brain injury: A normed comparison

Abstract: We examined, among those persons working preinjury, the risk of unemployment 1 year after traumatic brain injury (TBI) relative to expected risk of unemployment for the sample under a validated risk-adjusted econometric model of employment in the U.S. population. Results indicate that 42% of TBI cases were unemployed versus 9% expected, relative risk (RR) = 4.5, 95% confidence interval (CI) (4.12, 4.95). The relative risk for unemployment was higher among males, those with higher education, persons with more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 21 publications
4
56
0
2
Order By: Relevance
“…Brain injury has been associated with chronic illness, other disabilities, unemployment, and early death, including death by traumatic causes (Ackerman & Banks, 2009;Corrigan, Selassie, & Orman, 2010;Doctor et al, 2005;Hart et al, 2014;Langlois, Rutland-Brown, & Wald, 2006;Pogoda et al, 2016;Tanielian & Jaycox, 2008;Vaaramo, Puljula, Tetri, Juvela, & Hillbom, 2015).…”
Section: Sequelae Of Traumatic Brain Injuriesmentioning
confidence: 99%
“…Brain injury has been associated with chronic illness, other disabilities, unemployment, and early death, including death by traumatic causes (Ackerman & Banks, 2009;Corrigan, Selassie, & Orman, 2010;Doctor et al, 2005;Hart et al, 2014;Langlois, Rutland-Brown, & Wald, 2006;Pogoda et al, 2016;Tanielian & Jaycox, 2008;Vaaramo, Puljula, Tetri, Juvela, & Hillbom, 2015).…”
Section: Sequelae Of Traumatic Brain Injuriesmentioning
confidence: 99%
“…• Eight review articles [46][47][48][49][50][51][52][53] and 30 quantitative studies reporting factors associated with successful employment outcomes [1,2,. • Six qualitative studies addressing clients' experiences with return to work [82][83][84][85][86][87].…”
Section: Identification Of Guideline Objectives and Questionsmentioning
confidence: 99%
“…Consequently, a large proportion of individuals who have sustained brain injuries are unemployed or underemployed [2] with reported rates of return to work of approximately 40% 1-2 years post-injury [3]. Unemployment or underemployment following TBI can produce detrimental effects for individuals, their support system, and society [4] resulting in poor psychosocial outcomes, decreased community integration and increased economic dependence [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Coetzar et al [12] reported that individuals with moderate to severe TBI showed a significant change in their work status post-injury when compared to that of pre-injury. Among TBI survivors, the unemployment rate was reported to be substantially high [13,14].…”
Section: Introductionmentioning
confidence: 99%